Hemp seed cake fed to broilers - Kalmendal, Robin (2008)
The use of hemp seed cake (HSC) in a poultry nutritional context is described in this MSc thesis. It is well documented that HSC is distinguished by a high protein quality and a high proportion of unsaturated fatty acids. This, along with its palatability, claimed sustainability and advantageous crop rotational properties make HSC particularly interesting to the organic poultry production. Further, the presence of anti-nutritional factors is low. In the present study, a HSC digestibility trial was set up using 72 as-hatched 28 days old broiler chickens. Further, the growth and feed utilization efficiency was studied. Four experimental diets were composed by replacing 0, 10, 20 and 30 % of a commercial finisher feed with HSC. TiO2 was added as an indigestible marker. Ileal and excreta samples were collected and the digestibility data were subjected to linear regression analysis. An apparent metabolizable energy (AME) value of 13.8 MJ/kg DM was suggested and the ileal digestibilities of dry matter, protein, fat and starch were determined to 0.37, 0.80, 0.89 and 0.94, respectively. Generally, the statistical variance was larger in the excreta samples in comparison to the ileal samples. Thus some fibrous contents were assumed to be fermented in the caeca. The production parameters feed consumption; weight gain and feed conversion ratio were satisfactory and were not affected by the inclusion of HSC. It was concluded that the nutritional value of HSC partly resembles e.g. that of rape seed cake and that a 30 % inclusion rate showed no negative effects on the production nor the palatability of the feed when fed during the days 28-35 post-hatch.